The ant genus Pseudaphomomyrmex Wheeler, 1920 a junior synonym of Tapinoma Foerster, 1850 - Fisher, Brian L.; Bolten, Barry (Zootaxa, 2007)
Ashmead (1905) described a solitary alate queen ant, collected in the Philippines, as Aphomyrmex emeryi. The generic combination, obviously a misspelling of Aphomomyrmex Emery, 1899 (see Bolton, 1995) placed the name in the subfamily Formicinae. Wheeler (1920) disagreed with the generic combination and removed emeryi to its own monotypic genus, Pseudaphomomyrmex. He did not characterise the genus at that time but later (Wheeler, 1922: 695) included it in a key to Formicinae, thereby indicating which characters he considered diagnostic and apparently confirming its position in that subfamily. A short time later Emery (1925: 44) dismissed Pseudaphomomyrmex as a junior synonym of Aphomomyrmex but the name was later revived from synonymy, probably accidentally, by Chapman & Capco (1951: 214). From its description to the present Pseudaphomomyrmex has been placed in a number of different tribes, summarised in Bolton (2003), but always retained in subfamily Formicinae.